THE GUMREGAH BUNGAH PROGRAM'S INNOVATION IN ADDRESSING OUT-OF-SCHOOL CHILDREN IN MAGELANG REGENCY (CASE STUDY OF COLLABORATION BETWEEN AWWALIYAH TEGALREJO ISLAMIC BOARDING SCHOOL AND TAMAN DEWANTA COMMUNITY LEARNING CENTER) - Zaenal Afifudin; Mintarsih Arbarini (SOSIOEDUKASI, 2026)
This study aims to describe and analyze the handling of Out-of-School Children before the Gumregah Bungah Program, the form of program innovation, the form of collaboration between the Awwaliyah Tegalrejo Islamic Boarding School and the Taman Dewanta Community Learning Center (CLC), and the impact of the program on the handling of Out-of-School Children in Magelang Regency. The study uses a qualitative approach with a case study design. The research subjects include program managers, Islamic boarding school caretakers, CLC tutors, and Out-of-School Children students. Data collection techniques are carried out through observation, interviews, and documentation. Data validity uses triangulation of sources, techniques, and time, while data analysis uses the Miles and Huberman model through data reduction, data presentation, and drawing conclusions. The results of the study show that before the Gumregah Bungah Program, the handling of Out-of-School Children was still administrative and had not touched the social and psychological needs of students. The Gumregah Bungah Program is present as a community-based educational innovation through the integration of Islamic boarding schools and CLC in equivalency education services and character building. The form of collaboration is carried out through the division of roles between Islamic boarding schools as centers for moral and social development, and CLC as providers of equivalency education. This program has had positive impacts in the form of increased access to education for out-of-school children, increased motivation to learn, changes in students' social behavior, and enhanced self-confidence and character. The Gumregah Bungah program serves as a collaborative, humanistic, and inclusive model for addressing out-of-school children in Magelang Regency.